Fluid–structure interaction study of the start-up of a rocket engine nozzle. - Garelli, Luciano (2010)
The aim of this paper is to analyze the aeroelastic processes  developed during the starting phase of a rocket engine via a coupling fluid/structure code. This analysis gives a better understanding of the behavior of the structure as the shock waves propagate inside the engine nozzle. The gasdynamics Euler equations are solved for the fluid and constitutive linear elastic solid assuming large  displacements and rotations with no material damping is adopted for the structure. The coupling of each subproblem is carried out with a Gauß–Seidel algorithm over the fluid and structure states. For the fluid problem an ALE (Arbitrary Lagrangian–Eulerian) formulation is used. It allows us to define a reference system following the moving boundaries while the structure is deformed. The code is validated  with a study of the flutter phenomena that may occur when a supersonic compressible fluid flows over a flat solid plate. Regarding the rocket engine ignition problem, a modal analysis of the structure is performed in order to analyze the eigenfrequency shifts when considering the coupling with the fluid flow.